Development and optimization of a QuEChERS-GC-MS/MS methodology to analyse ultraviolet-filters and synthetic musks in sewage sludge - Sara Ramos (2019)
A Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) methodology followed by gas chromatography-triple quadrupole mass spectrometry (GC-MS/MS) analysis was developed to extract synthetic musk compounds (SMCs) (6 polycyclic, 2 macrocyclic and 5 nitro musks) and ultraviolet-filters (UVFs) (6 compounds) from sludge. This methodology fills a gap in the literature, since the proposed technique does not require specific equipment, nor large amounts of solvents, sorbents and time to extract SMCs and UVFs from sludge. To optimize this new methodology, a design of experiments (DoE) approach was used, applying first a screening design (SD) and then a central composite design (CCD). The best conditions achieved to extract these 19 compounds simultaneously were: 500 mg freeze dried sludge, 2.5 min of vortex and 15 min ultrasound and the use of a QuEChERS for the dispersive solid-phase extraction (d-SPE) containing 500 mg MgSO4, 410 mg C18 and 315 mg PSA. Then, this methodology was successfully validated. Recoveries of the target compounds ranged from 75% (cashmeran, DPMI) to 122% (2-ethylhexyl 4-methoxycinnamate, EHMC), with good repeatability (relative standard deviation < 10%). The instrumental detection limits (IDLs) and quantification (IQLs) varied from 0.001 pg (musk moskene, MM) to 7.5 pg (musk xylene, MX) and from 0.003 (MM) to 25 pg (MX), respectively. The method detection and quantification limits (MDLs and MQLs) ranged between 0.5 (DPMI) and 1394 (exaltolide, EXA) ng/g dw and 2 and 4648 ng/g-dw, respectively. Both SMCs and UVFs were detected in all sludge samples analysed. Higher concentrations were found for octocrylene (OC: maximum value of 115,486 ng/g-dw) followed by galaxolide (HHCB: 81,771 ng/g-dw). Only the nitro musks ambrette, xylene, moskene and tibetene and macrocyclic musk ethylene brassylate (EB) were not detected in any sample.